Pembelajaran Dalam Jaringan Mata Pelajaran Geografi Pada Masa Pandemi Covid-19 - Desiana; La Ode Amaluddin; La Ode Nursalam; Rahma Musyawarah (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2022)
Senior High School 10 Kendari is one of the high schools in Kendari that implements online learning during the Covid-19 pandemi. This study aims to: 1) describe the preparations made by Geography teachers in implementing online learning; and 2) describe the implementation of online learning during the Covid-19 pandemi. This type of research is descriptive qualitative with the research subject of Geography teachers at Senior High School 10 Kendari. The results showed that: 1) the preparations made before starting the lesson were preparing learning materials to be taught in the form of powerpoints and learning videos as well as preparing tools such as laptops and headsets; and 2) For the Geography subject, the implementation of online learning during the Covid-19 pandemi at Senior High School 10 Kendari was carried out face-to-face virtually using the Zoom application, starting from preliminary activities, core activities, closing activities to the assessment stage.